Fenomeni dissociativi in un campione di pazienti Borderline La patologia dissociativa come processo patogenetico nucleare del Disturbo Borderline di Personalità - 1 Daniela Cantone, 2 Filomena De Falco, 2 Tilde Annunziato, 2 Alfonso Davide Di Sarno, 2 Carmen Giannetti, 2 Daniela Iennaco, 2 Martina Messina, 2 Vincenzo Perrella, 2 Barbara Vitulano (Phenomena Journal)
Aims. This study aims to investigate the relationship between dissociative phenomena and the Borderline Personality Disorder, in order to identify which one of dissociative symptoms factor has a stronger tie with Borderline Personality Disorder. Moreover, this study aims to find out if the presence of dissociative symptoms is linked to the number of Borderline Personality Disorder traits (symptoms), or the Borderline Personality Disorder diagnosis itself. Methods. A representative sample (n = 1033) was selected from patients visiting a private mental health clinical center in Naples. Inclusion criteria provided both Borderline Personality Disorder and non-Borderline Personality Disorder patients. The Dissociative Experiences Scale and the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders IV Axis II Disorders were used in order to collect data. Statistical Analysis involved the Student’s T-test, logistic regression and one-way Analysis of Variance. Continuous variables were standardized before the regression test. In addition, collected data were analyzed by the software Statistical Package of Social Science. Results. The mean of DES-Total scores in Borderline Personality Disorder patients (μ = 17,38) was significantly higher (t = -3,11) than in non-Borderline Personality Disorder patients (μ = 10,72). Logistic regression showed a strong link between dissociative phenomena and Borderline Personality Disorder respect to DES Factor III (depersonalization/derealization). Furthermore, it shows how increasing one standard point in DES Factor III increases by 50% the chance to detect a Borderline Personality Disorder. Lastly, the Analysis of Variance highlighted that more the number of Borderline Personality Disorder traits increase, the higher average are shown on DES-Total scores. Discussion and conclusions. The study has shown that Dissociative phenomena are more frequent in Borderline Personality Disorder patients rather than non-Borderline Personality Disorder patients. Moreover, it shows that the link between dissociative phenomena and Borderline Personality Disorder is stronger in relation to symptom factor depersonalization/derealisation. Finally, results show that DES-Total mean scores increase as Borderline Personality Disorder traits number increases, with higher scores when four specific traits are detected. This evidence confirms that the relationship between dissociative phenomena and Borderline Personality Disorder depends on the number of Borderline Personality Disorder traits detected, but not necessarily on the Borderline Personality Disorder diagnosis.